2022
DOI: 10.3390/universe8060333
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the ‘Outliers’ Track in Black Hole X-ray Binaries with a BZ-Jet and Inner-Disk Coupling

Abstract: In this paper, we investigate the black hole (BH) spin contribution to jet power, especially for the magnetic arrested disk (MAD), where only inner accretion disk luminosity is closely coupled with the spin-jet power, and try to explain the ‘outliers’ track of the radio LR to X-ray luminosity LX in two black hole X-ray binaries (BHXBs). Our results suggest that the BZ-jet and the inner-disk coupling could account for the ‘outliers’ track of the radio/X-ray correlation in two BHXBs, H1743-322 and MAXI J1348-630… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Another component that is missing in this classical picture is the collimated jet [17], which can be a significant source of the X-ray emission in the hard state, and it is shown to dominate the X-ray emission in the quiescent state [18]. Recent studies showed that the jet contribution itself depends on the BH spin [19]. Reproduced with permission from Ramesh Narayan and ApJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another component that is missing in this classical picture is the collimated jet [17], which can be a significant source of the X-ray emission in the hard state, and it is shown to dominate the X-ray emission in the quiescent state [18]. Recent studies showed that the jet contribution itself depends on the BH spin [19]. Reproduced with permission from Ramesh Narayan and ApJ.…”
Section: Introductionmentioning
confidence: 99%
“…The 𝜒 values for the kerrbb fit turned out to be 𝜒 /dof = 2. 19 Apart from the difficulty fitting the spectrum using these models, there seems to be an inconsistency between the BH spin values obtained from the continuum fit and the iron-line fit. Since neither the mass, nor the distance were precisely known at the time, changing these values somewhat in the kerrbb model (13.5 Mʘ and 7.5 kpc) resulted in BH spin values 0.93 and 0.96 for the 2002 and 2003 datasets, respectively.…”
mentioning
confidence: 99%